2008
DOI: 10.5194/amt-1-1-2008
|View full text |Cite
|
Sign up to set email alerts
|

Surface features on Sahara soil dust particles made visible by atomic force microscope (AFM) phase images

Abstract: Abstract. We show that atomic force microscopy (AFM) phase images can reveal surface features of soil dust particles, which are not evident using other microscopic methods. The non-contact AFM method is able to resolve topographical structures in the nanometer range as well as to uncover repulsive atomic forces and attractive van der Waals' forces, and thus gives insight to surface properties. Though the method does not allow quantitative assignment in terms of chemical compound description, it clearly shows d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…More data sets are available from microscopy measurements, where the size range of atmospheric importance is covered by electron microscopy techniques like transmission and scanning electron microscopy (TEM/SEM). Atomic force microscopy (AFM) is also used, but limited to particles smaller than 1.5 µm in diameter (Gwaze et al, 2007;Chou et al, 2008;Helas and Andreae, 2008).…”
Section: Measuring Techniques To Determine Particle Shapementioning
confidence: 99%
“…More data sets are available from microscopy measurements, where the size range of atmospheric importance is covered by electron microscopy techniques like transmission and scanning electron microscopy (TEM/SEM). Atomic force microscopy (AFM) is also used, but limited to particles smaller than 1.5 µm in diameter (Gwaze et al, 2007;Chou et al, 2008;Helas and Andreae, 2008).…”
Section: Measuring Techniques To Determine Particle Shapementioning
confidence: 99%
“…More data sets are available from microscopy measurements, where the size range of atmospheric importance is covered by electron microscopy techniques like transmission and scanning electron microscopy (TEM/SEM). Atomic force microscopy (AFM) is also used, but limited to particles smaller than 1.5 µm in diameter (Chou et al, 2008;Gwaze et al, 2007;Helas and Andreae, 2008). The particle shape derived by microscopic techniques is usually derived from the two-dimensional outline of the particle.…”
Section: Measuring Techniques To Determine Particle Shapementioning
confidence: 99%
“…Surface roughness affects the scattering phase function especially for particles larger than the wavelength (Nousiainen and Muinonen, 2007 (Helas and Andreae, 2008) and airborne dust (Chou et al, 2008), but no systematic studies suitable for modelling purposes have been performed yet.…”
Section: Measuring Techniques To Determine Particle Shapementioning
confidence: 99%
“…However, limited AFM analysis of dust particles by Chou et al (2008) revealed that particles were remarkably smooth (see Chou et al's Figure 8). Similarly, Helas and Andreae (2008) also found that Saharan dust particles were smooth; the surface roughness was not quantified in either case.…”
Section: Introductionmentioning
confidence: 91%